PUBLIC AWARENESS AND POLICY RESPONSES TO TRANSNATIONAL FRAUD PARKS: EVIDENCE FROM A MALAYSIAN NATIONWIDE SURVEY - Lee, Jenn Yuan; Chin , Yee Mun; Tan , Sing Pei; Phua , Yeong Nan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Fraud parks—transnational scam compounds in Southeast Asia—pose acute challenges for security, governance, and human rights. Combining trafficking, forced labour, and cyber-enabled fraud, these hubs target victims globally while luring jobseekers from Malaysia and beyond. Despite media attention, systematic evidence on public awareness and policy expectations has been scarce. This article fills that gap through a nationwide multilingual survey conducted by the Tun Tan Cheng Lock Centre for Social and Policy Studies (TCLC) in late 2023. Findings show high awareness of fraud parks as systemic threats, but also persistent vulnerabilities: younger respondents underestimated risks from job offers and online relationships, and many reported knowing victims personally. Policy preferences were clear, with overwhelming support for stronger education, enforcement, institutional reform, NGO collaboration, and international cooperation. The results highlight the paradox of high awareness amid continuing victimisation, while underscoring public opinion as a mandate for integrated national and regional responses.